The Effect of Agricultural Extension and Post-Harvest Processing Technology in Increasing Farmers' Income and Farm Business Sustainability in Rural Bandung Regency - Eddy Silamat; Ari Permana Ginting; Eko Sutrisno (West Science Interdisciplinary Studies, 2024)
This study examines the impact of agricultural extension services and post-harvest processing technology on farmers' income and farm business sustainability in rural Bandung Regency. A quantitative analysis of 160 farmers' responses, measured using a Likert scale, revealed that agricultural extension services significantly enhance farm sustainability and increase farmers' income. Similarly, post-harvest processing technology positively impacts both farm sustainability and income. These findings underscore the importance of these interventions in promoting sustainable agricultural development and improving farmers' livelihoods, highlighting the need for continuous investment in agricultural extension programs and the promotion of post-harvest technologies to support rural agricultural communities.